2020
DOI: 10.7717/peerj.8501
|View full text |Cite
|
Sign up to set email alerts
|

Early-life intestinal microbiome in Trachemys scripta elegans analyzed using 16S rRNA sequencing

Abstract: During the early-life period, the hatchlings of red-eared slider turtles (Trachemys scripta elegans) rely on their own post-hatching internal yolk for several days before beginning to feed. The gut microbiome is critical for the adaptation of organisms to new environments, but, to date, how the microbiome taxa are assembled during early life of the turtle is unknown. In this study, the intestinal microbiome of red-eared slider hatchlings (fed on commercial particle food) was systematically analyzed at four dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Our work is the first on an Asian freshwater turtle species (family Geoemydidae). Our results for wild S. bealei at the phylum level was similar to one species (Graptemys psesudogeographica) (Butterfield, 2019) dominated by Proteobacteria, while different from other species (Chrysemys picta and Trachemys scripta elegans) (Fugate et al, 2019;Peng et al, 2020) dominated by Firmicutes. The limited amount of gut microbiota data for turtles and especially freshwater turtles prevents us from making any generalizations, but we hope that future studies will help us understand the host-microbiota relationship in turtles.…”
Section: Turtle Gut Microbiotasupporting
confidence: 65%
See 4 more Smart Citations
“…Our work is the first on an Asian freshwater turtle species (family Geoemydidae). Our results for wild S. bealei at the phylum level was similar to one species (Graptemys psesudogeographica) (Butterfield, 2019) dominated by Proteobacteria, while different from other species (Chrysemys picta and Trachemys scripta elegans) (Fugate et al, 2019;Peng et al, 2020) dominated by Firmicutes. The limited amount of gut microbiota data for turtles and especially freshwater turtles prevents us from making any generalizations, but we hope that future studies will help us understand the host-microbiota relationship in turtles.…”
Section: Turtle Gut Microbiotasupporting
confidence: 65%
“…A trend first found in humans, individuals with plant-based diets have gut microbiota dominated by taxa in the phylum Firmicutes that metabolize plant polysaccharides and degrade cellulose into volatile fatty acids, while animal-based diets are dominated by taxa in the phyla Proteobacteria that are bile tolerant (David et al, 2014). This pattern was also seen in turtle studies, with herbivorous species having gut microbiota dominated by Firmicutes (Gaillard, 2014;Modica, 2016;Fugate et al, 2019;Peng et al, 2020), while carnivorous and omnivorous species had gut microbiotas dominated by Bacteroidetes (Biagi et al, 2018;Bloodgood et al, 2020). In particular, Bloodgood et al (2020) showed that gut microbial diversity has the ability to change in relation to diet; when herbivorous green sea turtles (Chelonia mydas) were given an omnivorous diet (seafood + vegetables) in captivity, their gut microbiota shifted from being dominated by Firmicutes to Bacteriodetes.…”
Section: Comparison Of Wild and Captive Individualsmentioning
confidence: 70%
See 3 more Smart Citations